Cross‐Domain Trajectories of Students' Ability Self‐Concepts and Intrinsic Values in Math and Language Arts. Issue 5 (22nd November 2019) - Gaspard, Hanna; Lauermann, Fani; Rose, Norman; Wigfield, Allan; Eccles, Jacquelynne S.
Abstract : Different cross‐domain trajectories in the development of students' ability self‐concepts (ASCs) and their intrinsic valuing of math and language arts were examined in a cross‐sequential study spanning Grades 1 through 12 ( n  = 1, 069). Growth mixture modeling analyses identified a Moderate Math Decline/Stable High Language Arts class and a Moderate Math Decline/Strong Language Arts Decline class for students' ASC trajectories. Students' intrinsic value trajectories included a Strong Math Decline/Language Arts Decline Leveling Off, a Moderate Math Decline/Strong Language Arts Decline, and a Stable Math and Language Arts Trajectories class. These classes differed with regard to student characteristics, including gender, family background, and math and reading aptitudes. They also resulted in different high school math course enrollments, career aspirations, and adult careers.